Learning vocabulary through audiovisual input: The differential effect of L1 subtitles and captions. (December 2016) - Peters, Elke; Heynen, Eva; Puimège, Eva
Abstract: Recent research has shown that learners can learn new words while watching TV programs. However, the number of words learned tends to be low. Several studies have demonstrated that first language (L1) subtitles as well as captions (= subtitles in the foreign language) have the potential to increase learning gains compared to when no on-screen text aids are provided. However, the evidence regarding the differential effect of both types of subtitles is still inconclusive. This paper reports on two exploratory studies investigating the effect of L1 subtitles and captions on different aspects of word knowledge among English-as-a-foreign language (EFL) learners in Flanders (Belgium). Data were collected in two different educational settings: intermediate EFL learners from a general school and low-proficiency EFL learners from a vocational school. Although learning gains were generally low, results indicated that captions have the potential to increase form learning. However, learners who were exposed to the audiovisual input with L1 subtitles did not perform better than the captions group in the tests focusing on the meaning of the target items. Additionally, findings also suggested that learners' vocabulary size and an item's frequency of occurrence in the video clip correlated positively with word learning.